(untitled) (Comillas Journal of International Relations, 2015)
This paper analyzes the construction process of the eurozone as a monetary union without fiscal and banking union. Recent developments in the European currency area are studied, as well as the asymmetric shocks that have hit member economies. Furthermore, the article describes the adjustment followed by peripheral countries until the implementation of the Outright Monetary Transactions (OMT) program. Finally, the paper studies the different paths that the Eurozone recovery could take from 2015, highlighting its likely survival despite the institutional and economic convergence difficulties that have been found.